Price Dispersion and the Costs of Inflation - Volker Hahn (Journal of Money, Credit and Banking, 2021)
The new Keynesian literature typically makes the assumption that firms always have to satisfy demand, which is at odds with profit-maximizing behavior under Calvo pricing when long-run inflation is positive. Our model, which relaxes this assumption, predicts that inflation causes a substantially smaller loss in effective aggregate productivity compared to a benchmark model without the possibility of rationing. Moreover, under positive inflation, firms choose smaller markups over marginal costs in our model than in the benchmark model. As a result, our analysis suggests that the standard new Keynesian model may exaggerate the welfare costs of~inflation.
Keywords: 330; new Keynesian model; optimal inflation target; trend inflation; welfare costs of inflation